6*x+8=14+30               20 +4*x=52                    5*(x+4)-43=17

6*x+8=14+30               20 +4*x=52                    5*(x+4)-43=17
Гость
Ответ(ы) на вопрос:
Гость
6*x+8=14+30     6х= 44-8 6х = 36 х = 36/6  х = 6 20 +4*x=52    4х = 52 - 20 4х = 32 х = 32/4 х = 8 5*(x+4)-43=17 5х + 20 - 43 = 17 5х = 17-20+43 5х = 40 х = 40/5 х = 8
Гость
6*х+8=44        4*х=52-20           5*(х+4)=17+43 6*х=44-8          4*х=32               5*(х+4)=60 6*х=36            х=32:4                 х+4=60:5 х=36:6            х=8                     х+4=12 х=6                                            х=12-4                                                  х=8
Не нашли ответ?
Ответить на вопрос
Похожие вопросы